Analisis Kemampuan Operasi Hitung Penjumlahan dan Pengurangan pada Siswa Kelas II SD di Batangtoru : Faktor Kesulitan dan Upaya Guru - Panggabean, Dwi Utami; Caniago, Juliana Sari; Pefriani; Amir, Almira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the addition and subtraction arithmetic skills of second-grade elementary school students, identify the factors causing learning difficulties, and describe teachers’ efforts to improve students’ numeracy skills. This study employed a qualitative approach with a descriptive method. Data were obtained through documentation study and analysis of relevant learning sources, including lesson documents, student evaluation results, and academic references. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results showed that 71.4% of students (20 out of 28) were able to complete simple addition without the carrying technique, with an average score of 82.5. However, only 46.4% were able to correctly perform column addition with carrying, and only 39.3% could complete column subtraction with borrowing, indicating a significant gap between simple and column operations. The main difficulties stemmed from three interconnected factors: weak understanding of place value concepts, low learning motivation exacerbated by conventional teaching methods, and insufficient parental support at home. Teachers’ efforts included the use of concrete manipulative media, structured remedial programs that resulted in an average score improvement of 12 points, and interactive game-based learning activities. These findings suggest that innovative, student-centered, and sustainable learning strategies are essential to optimize elementary students’ arithmetic competence.